Genome Dynamics in Aging Mice - Dollé, Martijn E.T. (Cold Spring Harbor Laboratory Press, 2002)
Random spontaneous genome rearrangements are difficult to detect in vivo, especially in postmitotic tissues. Using a lacZ-plasmid reporter mouse model, we have previously presented evidence for the accumulation of large genome rearrangements in various tissues, including postmitotic tissues, during aging. These rearrangements, which were found to be organ-specific and to increase with age, have one breakpoint in the lacZ-reporter locus and the second elsewhere in the mouse genome. In this present work, we have used a mouse genome sequence database to physically characterize a total of 49 genome rearrangements in the brain, heart, and liver from young and old mice at two lacZ-plasmid reporter loci. Half of all breakpoints in the mouse genome occurred in chromosomes 3 and 4, each carrying a lacZ-reporter cluster, at distances varying from <100 kb to 66 Mb, indicating intrachromosomal deletions or inversions. The other half of the breakpoints in the mouse genome was found randomly on any of the other chromosomes, indicating translocations. Alternatively, part of the intra- and extrachromosomal events could involve transpositions. Regions of extended homology were not found at the breakpoints. These results lead us to postulate potential mechanisms for the origin of large genome rearrangements in mouse tissues and to predict their possible impact as a potential cause of aging.